Nutrition-sensitive agriculture: What have we learned and where do we go from here? - Ruel, Marie T.; Quisumbing, Agnes R.; Balagamwala, Mysbah (International Food Policy Research Institute, 2017)
A growing number of governments, donor agencies, and development organizations are committed to supporting nutrition-sensitive agriculture (NSA) to achieve their development goals. Although consensus exists on pathways through which agriculture may influence nutrition-related outcomes, empirical evidence on agriculture’s contribution to nutrition and how it can be enhanced is still weak. This paper reviews recent empirical evidence (since 2014), including findings from impact evaluations of a variety of NSA programs using experimental designs as well as observational studies that document linkages between agriculture, women’s empowerment, and nutrition. It summarizes existing knowledge regarding not only impacts but also pathways, mechanisms, and contextual factors that affect where and how agriculture may improve nutrition outcomes. The paper concludes with reflections on implications for agricultural programs, policies, and investments, and highlights future research priorities.